COVID‐19 vaccines: what do we know so far?. (19th July 2021) - Dhillon, Paraminder; Altmann, Daniel; Male, Victoria
Abstract : When the novel coronavirus was described in late 2019, it could not have been imagined that within a year, more than 100 vaccine candidates would be in preclinical development and several would be in clinical trials and even approved for use. The scale of the COVID‐19 outbreak pushed the scientific community, working in collaboration with pharmaceutical companies, public health bodies, policymakers, funders and governments, to develop vaccines against SARS‐CoV‐2 at record‐breaking speed. As well as driving major amendments to the usual timeframe for bringing a vaccine to fruition, the pandemic has accelerated the development of next‐generation technologies for vaccinology, giving rise to two frontrunner RNA vaccines. Although none of the critical safety and efficacy steps have been skipped within the compressed schedules, and the technologies underpinning the novel vaccines have been refined by scientists over many years, a significant proportion of the global population is sceptical of the benefits of COVID‐19 vaccines and wary of potential risks. In this interview‐based article, we give an overview of how the vaccines were developed and how they work to generate a robust immune response against COVID‐19, as well as addressing common questions relating to safety and efficacy. Abstract : The COVID‐19 outbreak has had a huge global impact, prompting the scientific community to develop a range of vaccines against the disease at an accelerated pace. Public reactions to the unprecedentedly rapid development and delivery of COVID‐19 vaccines have been mixed, with a significant minority expressing concerns about vaccine safety and efficacy. In particular, vaccines utilising relatively new mRNA‐based technology have come under intense scrutiny. Here, renowned immunologists Daniel Altmann and Victoria Male aim to clarify the science and alleviate concern by addressing several key questions relating to the development, mechanisms and effects of the vaccines.